Pediatric gastrointestinal stromal tumors—a review of diagnostic modalities - Quiroz, Hallie J.; Willobee, Brent A.; Sussman, Matthew S.; Fox, Bradley R.; Thorson, Chad M.; Sola, Juan E.; Perez, Eduardo A. (Translational Gastroenterology and Hepatology; Vol 3 (August 2018): Translational Gastroenterology and Hepatology, 2018)
Gastrointestinal stromal tumors are exceedingly rare tumors in the pediatric population, as a result many clinicians either may never see this diagnosis or will encounter it only a few times throughout their careers. It is imperative in the pediatric population to follow appropriate steps to ensure a swift diagnosis and referral to specialized centers that are equipped with the multidisciplinary teams accustomed to treating rare diseases. This review aims to discuss the most recent data available on the diagnostic modalities utilized in cases of suspected Pediatric GIST.